Yellow mealworm: effects of adults breeding density on adults and larvae performances from an industrial perspective - B. Palumbo; M. Cullere; Y. Singh; E. Pontalti; A. Dalle Zotte (Animal, 2024)
A key aspect to optimise the Tenebrio molitor (TM) farm productivity is to find an optimal breeding density for adults. To this purpose, this study investigated, from an industrial perspective, the impact of four breeding densities (D1, D2, D3 and D4, equal to 0.8, 1.1, 1.3 and 1.6 adults/cm2, respectively) on mortality and reproductive performances of TM adults and larvae. Two weeks after pupae emergence, TM adults were randomly assigned to the four groups and housed in 48 breeding crates (60 × 40 × 14.5 cm; 12 crates/group). The trial consisted of 4 consecutive weeks of adult breeding (each week represented one oviposition), and 8 weeks of larvae growth. From each week of oviposition, a batch of larvae was obtained for a total of four batches of larvae (48 crates/batch). Larvae of each batch were grown until 8 weeks of age, corresponding to the period required to reach the selling size. Larvae were kept in the original crates until the 5th weeks of age, after which they were divided into additional crates to ensure a density of 4.2 larvae/cm2 and a final weight of 1 500 g of larvae/crate (0.6 g of larvae/cm2). For each oviposition week, TM adult’s mortality, egg hatchability, BW, feed intake, chemical composition and fatty acid profile were evaluated, while ovary weight was measured at weeks 1 and 4. The number of larvae was monitored at week 5 of age while their chemical composition was determined at week 5 and 8. Larvae feed intake and BW were monitored over the 8-weeks growth period. Individual feed intake and BW of adults increased with increasing breeding density (P < 0.0001 and P < 0.05, respectively). With increasing adult breeding density, the number of larvae per crate increased (P < 0.001) while the grams of larvae/gram of adults decreased (R2 = 0.8856). Larvae from groups D2, D3 and D4 showed higher feed intake per crate and higher individual and total final BW than D1 (P < 0.001). However, the feed conversion ratio (FCR) worsened with increasing breeding density (P < 0.001). D4 larvae had higher percentages of protein (P < 0.001), lipids (P < 0.05) and cholesterol (P < 0.001) compared to larvae from other groups. Concluding, a breeding density of 0.8 adults/cm2 maximised both grams of larvae produced/grams of adults and larvae FCR. However, breeding densities above 0.8 adults/cm2 resulted in a higher number of produced larvae per crate with a greater final mass weight making a density of 1.6 adults/cm2 the preferable choice from and industrial perspective.